2016
DOI: 10.1039/c6dt00116e
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the binding strength of salicylaldoxime–uranyl complexes relative to competing salicylaldoxime–transition metal ion complexes in aqueous solution: a combined experimental and computational study

Abstract: The design of new ligands and investigation of UO2(2+) complexations are an essential aspect of reducing the cost of extracting uranium from seawater, improving the sorption efficiency for uranium and the selectivity for uranium over competing ions (such as the transition metal cations). The binding strengths of salicylaldoxime-UO2(2+) complexes were quantified for the first time and compared with the binding strengths of salicylic acid-UO2(2+) and representative amidoxime-UO2(2+) complexes. We found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 60 publications
5
32
0
Order By: Relevance
“…Thermodynamic analysis of complexation in aqueous environments can provide a further step towards understanding the differences in the performance of the studied polymers. To this end, the key thermodynamic parameters, such as p K a of the ligands and stability constants (log ß ) of the respective uranyl complexes, were computationally obtained through our recently developed protocols that achieve high accuracy in predicting aqueous p K a (root-mean-square deviation from experiment (RMSE) < 0.5 p K a units) 47 and log ß (RMSE < 1.0 log units) 48 (see the Methods section and Supplementary Fig. 16 and 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thermodynamic analysis of complexation in aqueous environments can provide a further step towards understanding the differences in the performance of the studied polymers. To this end, the key thermodynamic parameters, such as p K a of the ligands and stability constants (log ß ) of the respective uranyl complexes, were computationally obtained through our recently developed protocols that achieve high accuracy in predicting aqueous p K a (root-mean-square deviation from experiment (RMSE) < 0.5 p K a units) 47 and log ß (RMSE < 1.0 log units) 48 (see the Methods section and Supplementary Fig. 16 and 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using the gas-phase geometries, implicit solvent corrections were obtained at 298 K with the SMD 46 solvation model, as implemented in Gaussian 09, at the B3LYP/SSC/6-31 + G(d) level of theory. The preference for using a combination of the M06 and the B3LYP functionals with the SMD solvation model was based on the results of our previous studies 17 , 47 , which showed that the chosen levels of theory provide the best overall performance in predicting the log β values of uranyl 47 and vanadium 17 ions complexes with anionic oxygen and amidoxime donor ligands. Single-point coupled-cluster theory calculations, CCSD(T)/aug-cc-pvDZ (the valence electrons on C, O, H and the valence and subvalence electrons (3 s, 3p) on V were correlated), using M06/SSC/6-311 + + G(d,p) optimized geometries, were employed for selected V complexes with H 3 IDO and HAO ligands.…”
Section: Methodsmentioning
confidence: 99%
“…Among various possible interferences in a Zincon-based Zn 2+ assay, colorimetric response to copper ions (Cu 2+ ) is most cumbersome owing to the overlapping working pH range (8.5−9.5 for Zn 2+ ; 5.5−9.5 for Cu 2+ )[ 31 ] and similar maximum absorption wavelength of the colored metal-indicator complexes (620 nm for Zn 2+ , 600 nm for Cu 2+ )[ 31 ]. Salycilaldoxime, known as an effective chelating agent for Cu 2+ [ 32 , 33 , 34 ] as well as effective masking agent for other metal ions interfering the Zincon-based colorimetric Zn 2+ detection including Fe 2+ [ 35 , 36 , 37 ] and Ni 2+ [ 35 , 37 ], has been deposited on the glass fiber layers together with the buffer components (TAPS/TMAOH, pH = 8.5). Additionally, CuCl 2 has been placed on the topmost glass fiber layer for further suppressing interference from Cu 2+ (details are discussed in Section 3.2 ).…”
Section: Resultsmentioning
confidence: 99%